ISOLASI DAN IDENTIFIKASI BAKTERI POTENSIAL PROBIOTIK PADA SALURAN PENCERNAAN IKAN MAS (Cyprinus carpio) Isolation and Identification Potential Probiotic Bacteria in Digestive Tract of Goldfish (Cyprinus carpio) - Mikha Febryana Samosir; Dwi Suryanto; Desrita Desrita (AQUACOASTMARINE, 2017)
Probiotics are beneficial microbes to improve microbial balance in the digestive tract. The aims of this study was to isolate the potential probiotic bacteria in Goldfish (Cyprinus carpio). This study was conducted from May to October 2016 at the Fish Quarantine, Quality Control and Safety of Fishery Class I Medan I, Kuala Namu Medan. The isolation and identification of bacteria was carried out based on morphology and biochemistry tests. The result showed that the potential probiotic bacteria in the digestive tract of C. carpio was Micrococcus varians, Staphylococcus arlettae and Bacillus firmus.Keywords : C. carpio, identification, isolation, probiotic.